(untitled) (Journal of Social Sciences Review, 2023)
Pakistan is a multi-ethnic state, and as such, there has been a federal structure since its creation in 1947 to address ethnic issues effectively. The center-province relations have, however, suffered many ups and downs on certain issues, such as provincial autonomy and distribution of financial resources. The study in hand aims to investigate the relations between the Provincial Government of Khyber Pakhtunkhwa and the Federal Government of Pakistan at the center from 2008 to 2013. The focus here is on the PPPP-led government at the center and the ANP-led government in the Khyber Pakhtunkhwa province of Pakistan. The study proves that there was a significant improvement in the center-province relations in the case of the province of Khyber Pakhtunkhwa during the period under study. The introduction of the 18th Amendment to the constitution of Pakistan settled the longstanding issues of provincial autonomy and replaced the colonial name of the Province of North-West Frontier Province with Khyber Pakhtunkhwa. In the financial sphere, the 7th National Finance Commission (NFC) Award was a major achievement that enhanced the provincial share in financial resources. However, differences in the net-hydel profit could not be settled.